Cross-cultural adaptation of the Swedish version of Endometriosis Health Profile-30. (2nd October 2020) - Grundström, Hanna; Rauden, Anna; Olovsson, Matts
Abstract: The Endometriosis Health Profile-30 (EHP-30) is focusing on the effect of endometriosis symptoms upon health-related quality of life. The aim of this study was to pre-test and culturally adapt the Swedish version of EHP-30. Eighteen Swedish-speaking women with laparoscopically verified diagnosis of endometriosis answered the questionnaire and 17 were interviewed regarding their interpretations of the questionnaire. Demographics, distribution of answers, roof-ceiling effects and missing answers were analysed. The interviews were analysed using the qualitative approach proposed by Beaton et al. The Swedish version of EHP-30 was experienced as accessible with 100% data completeness and a roof effect (11%) in one dimension. Some women had difficulties with the instructions and one word should be replaced in order to culturally adapt the questionnaire. In conclusion, the Swedish version of EHP-30 is a useful and well-accepted questionnaire for women with endometriosis in Sweden, but a minor change of wording is recommended. Impact statement: What is already known on this subject? Cross-cultural adaptation and psychometric testing are crucial when introducing translated questionnaires. Cross-cultural adaptation is a process that looks at both translational and cultural issues when a questionnaire is being prepared for use in another country than the original. EHP-30 has been translated into Swedish but has not yet been cross-culturally adapted. What do the results of this study add? The Swedish version of EHP-30 was experienced as a useful and well-accepted questionnaire for women with endometriosis, but a minor change of wording is recommended in one question to make the questionnaire convergent with the original version. What are the implications of these findings for clinical practice and/or further research? The Swedish version of EHP-30 is user friendly and can be used in clinical practice after a minor change of wording. Then, it should also undergo psychometric testing.